Trace metal investigations in the fjords of Kiel Bight, Western Baltic Sea - data report of 1977/78 - Klaus Kremling; C Otto; Hauke Petersen (PANGAEA, 1979)
This data report includes the analytical results of about 220 water wamples collected at 33 stations in the Fjords of Kiel ,...